Utilisation of DNA barcoding for identification of fish products - G. Ahmad Faisal; M. N. Siti Azizah; M. N. Darlina (Syiah Kuala University, 2012)
DNA barcoding has been accepted nowadays as a globally accessible tool to delimitate and identify new species, as it can provide accurate and automated species identification through the use of standard gene, Cytochrome oxidase I (COI). As a result, DNA barcoding has become a perfect molecular tool to identify fish products and detect wrongly labelled fish in the market as it can identify fish species even without the presenceof complete morphological characteristics. Here we collected samples from sushi restaurants to investigate and identify the precise species identity of raw fish sushi products because most of them were labelled with only common names such as Tuna, Salmon and Butterfish without providing the scientific name of the fishes. Species identities of seven specimens from two sushi restaurants were DNA barcoded utilising the cytochrome oxidase I (COI) gene. The data were BLAST with GenBank and BOLD to confirm species identification. The results showed 100% matches that there was nosubstitution and wrongly labelling of species as the Salmon sushi matched the database sequences of Salmo salar, Tuna to Thunnus albacares and Butterfish to Lepidocybium flavobrunneum. The investigation of these fishproduct true identities should be carried out routinely to ensure consumer protection from mislabelling and substitution for a cheaper fishin order to avoid health issuessuch as allergic reaction due to intake of the wronglylabelled product